Blue Certificate as a Public Policy Innovation in Sustainable Coastal Destination Management in Bali - Putu Bagus Wisnuwardhana (LifeSciFi, 2026)
Mass tourism in Bali has severely degraded coastal environments, underscoring the need for sustainable policy innovation. This study aims to comprehensively analyze Blue Certificates as a public policy innovation designed to address these challenges. Using a systematic narrative literature review method with a policy analysis framework, this article synthesizes findings from relevant academic literature between 2019-2024. The results of the analysis show that Blue Certificates are an adaptive policy response that is in line with the global trend of using environmental certification instruments to encourage sustainable tourism practices. The review found that the effectiveness of these certifications does not depend solely on their technical design, but is crucially determined by their ability to be integrated in a collaborative governance ecosystem, involving governments, the private sector, and indigenous villages. It was also found that there is a significant gap in the literature related to empirical studies that specifically evaluate the impact of the implementation of Blue Certificates in Bali. In conclusion, the Blue Certificate has the potential to be an important instrument for the standardization of sustainable practices, but its success as a policy innovation depends on strengthening multi-stakeholder governance mechanisms and integrating them into more holistic coastal management strategies.